Unsteady behaviours of a volute in turbocharger turbine under pulsating conditions. (3rd November 2017) - Yang, Mingyang; Martinez-Botas, Ricardo F.; Rajoo, Srithar; Ibaraki, Seiichi; Yokoyama, Takao; Deng, Kangyao
Abstract: Turbochargers are currently in their prime utilization period, which pushes for performance enhancement from conventional turbochargers and more often than not revisiting its design methodology. A turbocharger turbine is subjected to pulsating flow, and how this feeds a steady flow design volute is a topic of interest for performance enhancement. This article investigates unsteady effects on flow characteristics in the volute of a turbine under pulsating flow conditions by numerical method validated by experimental measurement. A single pulse with sinusoidal shape is imposed at the turbine inlet for the investigation on unsteady behaviours. First, pulse propagation of different flow parameters along the volute passage, including pressure, temperature and mass flow rate, is studied by the validated numerical method. Next, the unsteady effect of the pulsating flow on the flow angle upstream the rotor inlet is confirmed by simulation results. The mechanism of this unsteady effect is then studied by an analytical model, and two factors for flow angle distributions are clearly demonstrated: the configuration of the volute A / R c and the unsteady effect that resulted from mass imbalance. This article demonstrates unsteady behaviours of the turbine volute under pulsating conditions, and the mechanism is discussed in details, which can lead to the improvement of volute design methodology tailoring for pulsating flow conditions.